2008
DOI: 10.1159/000254901
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nonpharmacological Interventions on Subjective Memory Complaints: A Systematic Review and Meta-Analysis

Abstract: Background: Subjective memory complaints (SMC) in the absence of psychiatric or neurological disorders are common among older adults. Although increasing numbers of individuals are suffering from SMC, research into interventions alleviating SMC is sparse. The present systematic review was conducted in order to present a clearer picture of the quality, quantity and outcomes of SMC intervention research. Methods: PubMed and PsychInfo were searched with a comprehensive search string delivering 4,496 hits. Abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 91 publications
(77 reference statements)
2
62
1
Order By: Relevance
“…Likewise, perceptions of low treatment control of SMCs may reflect the lack of knowledge of interventions available for memory problems such as memory retraining and cognitive restructuring (Metternich et al, 2010) rather than a negative belief about the efficacy of treatments. Timeline acute/chronic, timeline stability/decline, treatment control and illness coherence were not associated with distress.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, perceptions of low treatment control of SMCs may reflect the lack of knowledge of interventions available for memory problems such as memory retraining and cognitive restructuring (Metternich et al, 2010) rather than a negative belief about the efficacy of treatments. Timeline acute/chronic, timeline stability/decline, treatment control and illness coherence were not associated with distress.…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite being heterogeneously defined and assessed, 2 the concept of SCCs has growingly attracted clinical and research interest in the field of dementias and cognitive disorders for several reasons. First, SCCs represent a common condition in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Thus, a growing consensus has been reached which indicates SCCs as a ''promising'' stage for planning and implementing preventive interventions with the aim of reducing the incidence of cognitive disorders. 1,5 In this regard, dementia preventive trials are increasingly enrolling individuals with subjective complaints as target populations. 16,17 The implementation of preventive strategies requires specific adaptations, mainly due to the larger population to target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing effective interventions targeting compensatory mechanisms for agingrelated memory decline is therefore important. In a literature review, Metternich, Kosch, Kriston, Harter, and Hull (2010) concluded that compensatory cognitive training, aimed at acquiring and applying memory strategies, is effective in older adults. Whether this type of strategy training is particularly effective for older adults with a higher or lower CR should be investigated in further research.…”
Section: Discussionmentioning
confidence: 99%